A qualitative exploration of EAP practitioners’ materials-related challenges in the UK: contexts, constraints and consequences - Resheq, Susan (2024)
This qualitative study explores the materials-related challenges faced by English for Academic Purposes (EAP) practitioners in Pre-Sessional Programmes (PSP) at UK universities. Through semi-structured interviews with seven participants from four institutions, the research investigates the strategies employed to address these challenges and examines the underlying factors contributing to them. The study uncovers significant variations in approaches to EAP materials across institutions, ranging from integrated skills using authentic materials to more traditional skills-based approaches relying on commercial EAP textbooks. Key challenges identified include balancing generic and discipline-specific content, keeping materials up-to-date with rapidly evolving academic practices and technologies, and navigating institutional constraints. The research also highlights a critical lack of Continuous Professional Development (CPD) opportunities in materials development for EAP practitioners. Findings suggest that the effectiveness of EAP materials is influenced by materials instruction and broader issues of practitioner identity, institutional positioning of EAP, and the impact of neoliberal ideologies in Higher Education (HE). The study contributes to ongoing discussions about the nature and purpose of EAP materials and offers insights to inform future directions in EAP materials development and practitioner training.